2018
DOI: 10.1111/jgh.14466
|View full text |Cite
|
Sign up to set email alerts
|

Burden of hepatitis C virus infection in India: A systematic review and meta‐analysis

Abstract: Community-based data on HCV seroprevalence in India were limited. Large amount of data on blood donors and pregnant women were identified, with pooled anti-HCV seroprevalence rates of 0.44% and 0.88%, respectively. Among high-risk groups, anti-HCV prevalence was higher among people living with HIV, those with sexually transmitted diseases, high-risk sex behavior or injection drug use, and those receiving hemodialysis or frequent transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…[6][7][8][9][10] One systemic review found prevalence of HCV (anti-HCV) to be 0.85% in community-based studies, 0.44% in blood donors and 0.88% among pregnant women in India. 3 In our study, the prevalence of HCV infection is 0.05% overall and 0.02% among pregnant women. It is less than other reports from different parts of India, West Bengal (0.87%.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…[6][7][8][9][10] One systemic review found prevalence of HCV (anti-HCV) to be 0.85% in community-based studies, 0.44% in blood donors and 0.88% among pregnant women in India. 3 In our study, the prevalence of HCV infection is 0.05% overall and 0.02% among pregnant women. It is less than other reports from different parts of India, West Bengal (0.87%.…”
Section: Discussionmentioning
confidence: 52%
“…2 One systemic review found prevalence of HCV (anti-HCV) to be 0.85% in community-based studies, 0.44% in blood donors and 0.88% among pregnant women in India. 3 HCV infection is associated with significant morbidity and mortality. The clinical spectrum of HCV infection spreads widely from asymptomatic infection to chronic liver disease, liver cirrhosis, liver failure and hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…HCV infection is not evenly distributed geographically [7]. Reasons for south Punjab's higher HCV prevalence are uncertain but could be due to poorer infection control practices, more syringe re-use or unreported IDU.…”
Section: Discussionmentioning
confidence: 99%
“…However, as India's population is 1.3 billion, the country contains approximately 10 million people living with HCV [6]. Despite a recent systematic review [7], the Indian HCV burden is poorly described because of a paucity of community-level data [7]. …”
Section: Introductionmentioning
confidence: 99%
“…Globally an estimated 71 million individuals are infected with HCV out of which India is one of the six countries (others being China, Pakistan, Nigeria, Egypt & Russia) where more than 50% of the infected population resides [2] . A recent meta-analysis of HCV infection in Indian population predicted around 3 -9 million persons with active Hepatitis C infection [3].…”
Section: Introductionmentioning
confidence: 99%